Pengaruh Komposisi Kompos Tkks, Abu Boiler dan Trichoderma Terhadap Pertanaman Kedelai Pada Sela Tegakan Kelapa Sawit Yang Telah Menghasilkan di Lahan Gambut - Ricki Arianci; Nelvia '; Idwar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aims to obtain doses of the empty palm bunches of compost and ash of the boiler optimum for growth of soybean plant interposed in oil palm already produce in peat. This research conducted by using draft experimentally random group comprising nine of treatment and three of deut so acquired twenty seven units of the plot experiment. On the first of the plot unit experiment there were twenty plants and taken a sample of plants as many as five plant of the population of the plot at random to observation. Parameters used in this research is tall plant (cm), how many branches primary (strands), age flowering (day), the number pods, the number pods pithy, heavy dry 100 seeds of gram (g) and heavy dry of plot (g). The results showed that the high parameter, the number of primary branches of plants, flowering age, number of pods of pithy and dry weight of 100 seeds showed a different result is outcome real. However, on the parameter the number of pods and heavy dry of plot show a different outcome real. The best treatment in this research is treatment H ( 1,45 kg bunches of empty oil palm + 145 g ashes of the boilers + 2.9 g Trichoderma) of a plot that tends to increase high in plant, speed up the age of flowering, increase the number of pods and dry weight of the soybean plant. Key word : Empty Palm Bunches of Compost, Soybean, Peat Soil, Boiler, Trichoderma